Therapeutic Ultrasound in Dentistry Applications for Dentofacial Repair, Regeneration, and Tissue Engineering (Springer International Publishing, 2018)
This book highlights the potential of low-intensity pulsed ultrasound, or LIPUS, to introduce a new era in dentistry by revolutionizing the approach to dental treatment and providing a cure for pathologic conditions long considered untreatable. Readers will find information on all aspects of LIPUS, from its mode of action and biologic mechanisms to the full range of emerging clinical applications. The role of LIPUS in promoting dental tissue repair and regeneration and in tissue engineering is fully explained in a series of chapters focusing on stimulation of cell metabolism in the dentocraniofacial region, bone healing, periodontal regeneration, the temporomandibular joint, pulp cell differentiation, the salivary glands, and orthodontics. The past two decades have witnessed numerous discoveries that have enhanced the scope for use of therapeutic ultrasound in dentistry. In summarizing the latest knowledge in this exciting field, the book will be of interest to dental surgeons, orthodontists, periodontists, and other practitioners.